FAKTOR RESIKO WANITA OBESITAS PADA STATUS SOSIAL EKONOMI MENENGAH KE BAWAH - Dwi Novri Supriatiningrum (Ghidza Media Jurnal, 2021)
The prevalence of obesity is higher in women than in men. Based on the 2018 Riskesdas, the prevalence of obesity in women is 29.8% compared to men’s 14.7%. Obesity occurs due to many factors, mainly due to imbalance of energy or food intake with energy expenditure. This research is to determine LDL cholesterol, HDL, triglyceride, and body fat composition. The research design used in this study is a cross-sectional study design that aims to analyze obesity levels of LDL cholesterol, HDL, triglycerides, and fat composition with obesity. The mean fasting blood sugar level is 1.12 ± 0.33 mg / dl, mean blood sugar 2 hours PP 1.24 ± 0.44 mg / dl, the average HDL cholesterol level is 1.71 ± 0.47 mg / dl, the average LDL cholesterol level 1.53 ± 0.51 mg / dl, mean triglyceride cholesterol level 1.88 ± 0.49 mg / dl, mean blood pressure 1.59 ± 0.88 mmHg and mean fat composition 4.82 ± 0, 39% BB. Twenty-four percent of obese women have blood sugar levels above normal values. Fifty-three percent of obese women have LDL cholesterol levels above normal values. Six percent of obese women have high cholesterol levels. Each six percent of obese women have stage 1 hypertension and stage 2 hypertension. Eighty-two percent of obese women have a fat composition in the very risk category.